1994
DOI: 10.1177/875687059401300405
|View full text |Cite
|
Sign up to set email alerts
|

Special Education, School Psychology, and Community Mental Health Practice in Rural Settings: Common Problems and Overlapping Solutions for Training

Abstract: Rural service delivery issues common to the fields of special education, school psychology, and community mental health are described within this article. Many problems common across the three disciplines have some parallel solutions, and a number of potential solutions are suggested. Given preparation at the preservice level appears to be an effective starting point for preparing practitioners to deal with specific problems, the focus of these training-based solutions is at the preservice training level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1996
1996
2003
2003

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The lack of trained and qualified personnel working in rural areas is confounded by difficulties with teacher recruitment and retention (Gold, Russell, & Williams, 1993;Lemke, 1994;Ludlow, 1996;Merrell, et al, 1994;Ryan, 1999;Savelsbergh, 1995;Williams, Gold, & Russell, 1995). Reasons for initial recruitment difficulties include: geographic and social isolation (Sealander, Eigenberger, Peterson, Shellady, & Prater, 2001); limited availability of training and resources (Keiper & Busselle, 1996;Westling & Whitten, 1996); and competition with higher paying jobs in more attractive urban and suburban areas (Helge, 1992;Lemke, 1995).…”
Section: Special Education Staffing In Rural Communitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of trained and qualified personnel working in rural areas is confounded by difficulties with teacher recruitment and retention (Gold, Russell, & Williams, 1993;Lemke, 1994;Ludlow, 1996;Merrell, et al, 1994;Ryan, 1999;Savelsbergh, 1995;Williams, Gold, & Russell, 1995). Reasons for initial recruitment difficulties include: geographic and social isolation (Sealander, Eigenberger, Peterson, Shellady, & Prater, 2001); limited availability of training and resources (Keiper & Busselle, 1996;Westling & Whitten, 1996); and competition with higher paying jobs in more attractive urban and suburban areas (Helge, 1992;Lemke, 1995).…”
Section: Special Education Staffing In Rural Communitiesmentioning
confidence: 99%
“…Institutions of higher education have attempted to respond to the personnel needs of schools in rural areas in numerous ways: (a) using a teacher education model that requires faculty to travel to remote sites where preservice students have gathered from rural areas for courses needed for certification (Ludlow, Bloom, & Weinke, 1990;Merrell, et al, 1994;Savelsbergh, 1995;Sealander et al, 2001); (b) developing alternative certification programs (Sindelar, 1995;Zumwalt, 1991); (c) utilizing intensive summer institutes to provide extensive coursework in shortened time periods (Cheney & Demchak, 1999;Demchak & Cheney, 1995); and (d) implementing distance education programs through the use of technology (Ludlow, 1996;Lundin, 1994;Shrestha & Sutphin, 1995-96;Williams, Gold & Russell, 1995).…”
Section: Rural Teacher Preparationmentioning
confidence: 99%
“…In addition to having an impact on HIV prevention education in schools, unique aspects of rural life can also affect the delivery of special education programs. Challenges such as geographical distance between people and buildings, lack of access to resources, lack of specialists, difficulty in recruiting and retaining staff, and high poverty levels are frequently faced by rural administrators and special educators (Merrill et al, 1994).While limited research has been conducted related to health education for students in special education programs (Brantlinger, 1992;Everett, Price & Telljohann, 1994;Newins & McEwan 1995;Rabak-Wagener, Ellery, & Stacy, 1997), a review of literature revealed no studies specific to HIV prevention education for rural students in special education programs. The purposes of this study were: (a) to determine the level of implementation of HIV prevention education for students with mental retardation in rural schools in Indiana, (b) to identify barriers and supporting factors related to implementation, and (c) to identify pertinent staff development needs of special educators.…”
mentioning
confidence: 99%